Homozygote CRIM1 variant is associated with thiopurine-induced neutropenia in leukemic patients with both wildtype NUDT15 and TPMT - Yoomi Park; Hyery Kim; Heewon Seo; Jung Yoon Choi; Youngeun Ma; Sunmin Yun; Byung-Joo Min; Myung-Eui Seo; Keon Hee Yoo; Hyoung Jin Kang; Ho Joon Im; Ju Han Kim (Journal of Translational Medicine, 2020)
Abstract Background NUDT15 and TPMT variants are strong genetic determinants of thiopurine-induced hematological toxicity that results in therapeutic failure in pediatric acute lymphoblastic leukemia (ALL). However, many patients with both wild-type (WT) NUDT15 and TPMT still suffer from thiopurine toxicity and therapeutic failure. Methods Whole-exome sequencing was done for discovery (N = 244) and replication (N = 76) cohorts. Age- and sex-adjusted multiple regression analyses of both WT patients were performed to identify (p < 0.01, N = 188 for discovery) and validate (p < 0.05, N = 52 for replication) candidate variants for the tolerated last-cycle 6-mercaptopurine (6-MP) dose intensity percentage (DIP). Both independent and additive effects of the candidate variants on well-known NUDT15 and TPMT were evaluated by multigene prediction models. Results Among the 12 candidate variants from the discovery phase, the rs3821169 variant of the gene encoding Cysteine-Rich Transmembrane BMP Regulator 1 (CRIM1) was successfully replicated (p < 0.05). It showed high interethnic variability with an impressively high allele frequency in East Asians (T = 0.255) compared to Africans (0.001), Americans (0.02), Europeans (0.009), and South Asians (0.05). Homozygote carriers of the CRIM1 rs3821169 variant (N = 12, 5%) showed significantly lower last-cycle 6-MP DIPs in the discovery, replication, and combined cohorts (p = 0.025, 0.013, and 0.001, respectively). The traditional two-gene model (NUDT15 and TPMT) for predicting 6-MP DIP < 25% was outperformed by the three-gene model that included CRIM1, in terms of the area under the receiver operating characteristic curve (0.734 vs. 0.665), prediction accuracy (0.759 vs. 0.756), sensitivity (0.636 vs. 0.523), positive predictive value (0.315 vs. 0.288), and negative predictive value (0.931 vs. 0.913). Conclusions The CRIM1 rs3821169 variant is suggested to be an independent and/or additive genetic determinant of thiopurine toxicity beyond NUDT15 and TPMT in pediatric ALL.